Effect of forced swimming stress on count, motility and fertilization capacity of the sperm in adult rats - Ghasem Saki; Fakher Rahim; Karim Alizadeh (Wolters Kluwer Medknow Publications, 2009)
Aims: The purpose of this study was to determine whether 50 days of forced swimming stress applied to adult male rats affects count, motility and fertilization capacity of sperm. Settings and Design: It is a prospective study designed in vitro. Materials and Methods: A total 30 adult male wistar rats were used in this study. All rats were divided into two equal groups (n = 15): (1) control group and (2) experimental group. Animals of the experimental group were submitted to force swimming stress for 3 min in water at 32°C daily for 50 days. Then, all male rats were sacrificed, the right epididymides were removed and sperm concentration and motility were determined. The sperm suspension was added to the ova. Fertilization capacity was assessed by counting two-cell embryos 24-26 h after completion of fertilization in vitro. Statistical Analysis Used: Data are reported as mean ± SD and percentage. The difference between the control and experimental groups was determined by the unpaired t-test. Results: The mean and standard deviation of sperm concentration in the control and experimental groups were 60.8 ± 9.3 10 6 /ml and 20.4 ± 5.3 10 6 /ml, respectively. There was a statistical difference of P < 0.05 between the two groups in terms of sperm concentration. The percentage of motility in the experimental group was significantly different ( P < 0.05). The same results were obtained in case of fertility ( P < 0.05). Stress caused by forced swimming was observed by a significant increase in the latency of the pain response in the hot-plate test ( P < 0.05). Conclusions: These results suggest that forced swimming stress in time course equal or more than spermatogenesis period, i.e. 48-50 days in the rat will be significantly effective to reduce the number and motility of sperms as well as the fertilization capacity.